2016
DOI: 10.1111/jcmm.12986
|View full text |Cite
|
Sign up to set email alerts
|

Genistein suppresses leptin‐induced proliferation and migration of vascular smooth muscle cells and neointima formation

Abstract: Obesity is a strong risk factor for the development of cardiovascular diseases and is associated with a marked increase in circulating leptin concentration. Leptin is a peptide hormone mainly produced by adipose tissue and is regulated by energy level, hormones and various inflammatory mediators. Genistein is an isoflavone that exhibits diverse health‐promoting effects. Here, we investigated whether genistein suppressed the atherogenic effect induced by leptin. The A10 cells were treated with leptin and/or gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Further, leptin is able to induce production of C-reactive protein by endothelial cells [24]. The increase local availability of leptin in the vascular wall can in turn exert pro-atherothrombotic effects both on endothelial cells and smooth muscle cells [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Further, leptin is able to induce production of C-reactive protein by endothelial cells [24]. The increase local availability of leptin in the vascular wall can in turn exert pro-atherothrombotic effects both on endothelial cells and smooth muscle cells [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, isoflavone evidently inhibits both MMP-2 overproduction and elastin destruction, thereby exerting a protective effect against the progression of vascular injury. The capacity of isoflavone to suppress MMP-2 expression may be associated with the inhibition of p44/42 mitogen-activated protein kinases MAPK pathways 25 and nuclear factor kappa B NF-κB activities 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one young, adult male C57BL/6 mice, aged 3 weeks, were obtained from Japan SLC, Inc., Shizuoka, Japan. The mice were randomly placed in separate cages, under controlled conditions of a 12 h light/dark cycle at 25 1 . Prior approval for all animal experiments was obtained from the Kindai University Animal Care and Use Committee and the trials were carried out according to Kindai University Animal Experimentation Regulations approval number; KAAG-25-002 .…”
Section: Animals Experimental Protocol and Dietary Treatmentmentioning
confidence: 99%
“…SMC migration and proliferation are key events central to the progression of atherosclerosis. A growing body of literature [ 39 , 42 , 105 , 106 , 107 , 108 ] supports the growth-promoting effects of leptin on VSMC that may likely attribute to leptin-induced neointimal growth, vessel remodeling and atherosclerosis. Previous studies have reported that leptin stimulates VSMC proliferation via increased cell cycle progression to S and G2/M phases accompanied with augmented ERK1/2 and NF-kB activation [ 105 ].…”
Section: Leptin and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Previous studies have reported that leptin stimulates VSMC proliferation via increased cell cycle progression to S and G2/M phases accompanied with augmented ERK1/2 and NF-kB activation [ 105 ]. Leptin-induced cell cycle regulation has been shown to be mediated via increased expression of Cyclin D1 and β-catenin (regulator of cell–cell adhesion) concomitant to reduced p21 WAF1/Cip1 (promotes cell cycle arrest) [ 107 , 108 ] expression. Leptin has also been documented to increase VSMC migration mediated via enhanced matrix metalloproteinase-9 (MMP-9) expression [ 107 ].…”
Section: Leptin and Vascular Smooth Muscle Cellsmentioning
confidence: 99%